Association of NTCP polymorphisms with clinical outcome of hepatitis B infection in Thai individuals - Natthaya Chuaypen; Nongnaput Tuyapala; Nutcha Pinjaroen; Sunchai Payungporn; Pisit Tangkijvanich (BMC, 2019)
Abstract Background Single nucleotide polymorphisms (SNPs) in the sodium taurocholate co-transporting polypeptide (NTCP) have been showed to be associated with natural history of hepatitis B virus (HBV) infection. However, it is unclear whether the SNPs are related to the clinical outcome of HBV infection in Thai individuals. Methods The rs2296651 and rs4646287 polymorphisms of NTCP were determined by allelic discrimination using commercial TaqMan probes in blood samples of 1021 Thai individuals. These subjects included 610 patients with chronic HBV infection [CHB, 305 with hepatocellular carcinoma (HCC) and 305 without HCC], 206 subjects with spontaneous HBV clearance and 205 healthy controls who were age and gender-matched. Results The frequencies of rs2296651 A minor allele in the CHB group, the HBV clearance group and healthy controls were 7.8, 7.3 and 13.9%, respectively. For rs4646287, the frequencies of T minor allele of the corresponding groups were 10.4, 8.0 and 9.5%, respectively. Compared with healthy controls, the frequencies of rs2296651 GA + AA genotypes were significantly lower in the CHB group (P < 0.001) and in the HBV clearance group (P = 0.001). There was no difference in their distribution between the HBV clearance and CHB groups. Among the CHB group, the distribution of GA + AA genotypes in patients with HCC were significantly lower than in patients without HCC (P = 0.014). The frequencies of HBeAg positivity in patients harboring GG and GA + AA genotypes were 39.8 and 23.5%, respectively (P = 0.004). Among patients with HCC, the mean HBV DNA of the corresponding genotypes were 4.9 ± 1.3 vs. 2.7 ± 1.0 log10 IU/mL, respectively (P < 0.001). There was no difference in genotype and allele frequencies of rs4646287 polymorphism among all studied groups. Conclusions Our results showed that rs2296651 polymorphism was associated with a decreased risk of susceptibility to HBV infection and the development of HCC. These data suggest that the NTCP polymorphism might have an influence on natural history of HBV infection in Thai individuals. This abstract was partly presented at the American Association for the Study of Liver Diseases (AASLD) Meeting 2018, November 9-13, 2018, in San Francisco, CA, USA and was published in Hepatology 2018; 68:1237A-1238A.